Mahkota Dewa Mesocarp Infusion Improved Testicular Damage and Sperm Count In Diabetic Rat - Sulistyoningrum, Evy; Setiawati, Setiawati; Nindyastuti, Herlina; Putra, Adrian Nugraha (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2012)
Background: Global prevalence of Diabetes Mellitus (DM) is predicted to be increasing with worldwide population increase, longer life expectancy, urbanization, change in lifestyle and higher incidence of obesity. Diabetes Mellitus which is characterized by increasing level of blood glucose can induce increasing activity of ROS (Reactive Oxygen Species) which can further lead to abnormality in male reproductive system, especially testis. Mahkota dewa (Phaleria macrocarpa (Scheff.) Boerl.=PM) contain flavonoid, alkaloid and saponin which can prevent further negative effect on ROS increase in male reproductive system. The aim of this study was to know effect of PM mesocarp infusion on testicular damage and sperm count in alloxan induced diabetic rat.Design and Method: The design of this study was post test only with control group design. Rats in this study were divided into 4 groups (6 rats each group): control group, diabetic group, diabetic group treated with PM mesocarp infusion (9% and 13.5%). Diabetes was induced by alloxan 50 mg/BW single dose injection intramuscularly. PM mesocarp’s infusion was given in 4 weeks. Testicular damage was observed in hematoxylin-eosin stain using Johnsen criteria for spermatogenesis level and tubulus seminiferous’ diameter. Sperm count was performed on the semen taken from vas defferens using Giemsa stain.Result: PM mesocarp infusion group has higher spermatogenic level (p < 0,05), higher tubulus seminiferus diameter and sperm count (p < 0,05) than diabetic group.Conclusion: Mahkota dewa mesocarp infusion improved testicular damage and sperm count in alloxan-induced diabetic rat (Sains Medika, 4(2):115-123).